Association of heparin-induced skin lesions, intracutaneous tests, and heparin-induced IgG - Harenberg, Job; Huhle, Günter; Wang, Lianchun; Hoffmann, Ursula; Bayerl, Christiane; Kerowgan, Mohammed (Allergy, 1999)
Background: Cutaneous heparin-induced allergic reactions to subcutaneous heparin may begin 2-5 days after administration. The relation of the delayed-type hypersensitivity and a systemic immunologic response is controversial. The present investigation aimed to analyze the occurrence of thromboembolic complication, pathologic heparin-induced platelet activation (HIPA), and the presence of circulating heparin-induced IgG in patients with heparin-induced skin reactions. Methods: Intracutaneous tests, HIPA assay, and heparin-heparin IgG antibodies were performed in nine patients with heparin-induced skin lesions. Results: Six of eight patients showed positive intracutaneous tests to heparin and to four low-molecular-weight heparins. Three of six heparin-positive patients presented hypersensitivity to a heparinoid, too. Two of three patients had a positive HIPA test and elevated heparin-induced IgG antibodies. Both patients developed complications presenting as heparin-induced skin necrosis or arterial thrombosis. Two of nine patients were treated with danaparoid, 4/9 patients received r-hirudin, and 1/9 received oral coumarin. In 2/9 patients, anticoagulant therapy was stopped, but these patients will receive r-hirudin if indicated. Conclusions: On the basis of the coincidence of local and systemic hyperreactivity to heparin and danaparoid, patients with heparin-induced skin lesions should receive r-hirudin, a nonheparin compound, for anticoagulant treatment.